Woodsong: three-times newbery honor author - Paulsen, Gary (New York : SCHOLASTIC INC., 1991)
Gary Paulsen, three-time Newbery Honor author, is no stranger to adventure. He has flown off the back of a dogsled and down a frozen waterfall to near disaster, and waited for a giant bear to seal his fate with one slap of a claw. He has led a team of sled dogs toward the Alaskan Mountain Range in an Iditarod-the grueling, 1180-mile dog sled race-hallucinating from lack of sleep, but determined to finish. Here, in vivid detail, Paulsen recounts several of the remarkable experiences that shaped his life and inspired his award-winning writing.
Gary Paulsen, tres veces autor de Newbery Honor, no es ajeno a la aventura. Ha volado desde la parte trasera de un trineo de perros y por una cascada helada hasta casi el desastre, y ha esperado a que un oso gigante selle su destino con una palmada. Dirigió a un equipo de perros de trineo hacia la Cordillera de Alaska en un Iditarod, el agotador trineo de perros de 1180 millas, alucinando por la falta de sueño, pero decidido a terminar. Aquí, con vívido detalle, Paulsen relata varias de las experiencias extraordinarias que dieron forma a su vida e inspiraron su galardonada escritura.
Keywords: LITERATURA NORTEAMERICANA -- NOVELA; NORTH AMERICAN LITERATURE -- NOVEL